1994
DOI: 10.1172/jci117159
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to opacity proteins (Opa) correlate with a reduced risk of gonococcal salpingitis.

Abstract: Acute salpingitis complicating cervical gonococcal infection is a significant cause of infertility. Relatively little data are available concerning the pathophysiologic mechanisms of this disease. Clin. Invest. 1994. 93:1748-1755.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 44 publications
3
29
0
1
Order By: Relevance
“…They also reported that urethral infection by gonococci induced anti-LOS IgG in six of nine patients who had no detectable Ab in their preinfection sera. The importance of serum antibodies in the course of gonococcal infection has been reported by Plummer et al, who have shown that antibodies against selected gonococcal surface antigens can either increase or decrease the susceptibility to disease (31,32). Furthermore, the specificity of serum and local antibodies of female patients have been analyzed (14,20), and IgG and IgA against pili, LOS, porin protein I, and opacity proteins have been detected in both serum and vaginal fluids.…”
Section: Vol 78 2010 Los Contains Epitopes Recognized By Human Antimentioning
confidence: 90%
“…They also reported that urethral infection by gonococci induced anti-LOS IgG in six of nine patients who had no detectable Ab in their preinfection sera. The importance of serum antibodies in the course of gonococcal infection has been reported by Plummer et al, who have shown that antibodies against selected gonococcal surface antigens can either increase or decrease the susceptibility to disease (31,32). Furthermore, the specificity of serum and local antibodies of female patients have been analyzed (14,20), and IgG and IgA against pili, LOS, porin protein I, and opacity proteins have been detected in both serum and vaginal fluids.…”
Section: Vol 78 2010 Los Contains Epitopes Recognized By Human Antimentioning
confidence: 90%
“…The hallmark of humoral immune response against N. gonorrhoeae is the extremely low levels of antigonococcal antibodies found in serum and secretions of the human (male and female) during infection (19,20). Antibodies are directed against several major membrane molecules, such as the pilusand opacity-associated outer membrane proteins (Pil and Opa, respectively), the porin protein (Por), and the lipooligosaccharide (5,19,20,38,39,55). Although some of these have bactericidal activity, they are not protective and seem to be blocked by outer membrane protein 3 (RmP)-specific immunoglobulin Gs (IgGs) (38).…”
mentioning
confidence: 99%
“…The vaccine was contaminated with other outer membrane components; at least one that was present (Rmp antigen) is known to subvert the killing function of the Por-specific immune response (14). In the Por vaccine study, and in several additional contemporaneously performed natural history studies in women, modeling of the immune status of subjects exposed to N. gonorrhoeae has suggested that immunity against several outer membrane components together may predict protection from infection (15,16) or, alternatively, may enhance the likelihood of infection (17), depending on the relative contributions of specific immune responses. Therefore, a successful vaccine may have to be multivariate, targeting conserved epitopes while avoiding subversive immunogens.…”
Section: Session 3: Human Studiesmentioning
confidence: 99%